Isolation , Partial Characterization of a Dihydroflavonol From Sudanese Wetheria indica L.(Sterculiaceae) Stems and Biological Activity of the Ethanol Extract - Karim, Mohamed Abdel; Nousiba,M.,; Dalia,O., (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2019)
Phytochemical screening of Wetheria indica stems revealed the presence of flavonoids, tannins steroids , saponins and alkaloids. A flavonoid - compound (I)- was isolated from ethanol extract by thin layer chromatography and its structure was partially characteized on the basis of its spectral data (IR, UV, NMR ). The ethanol extract of Wetheria indica stems was evaluated for antimicrobial activity and it showed moderate activity against all test organisms. Also the extract exhibited significant free radical scavenging capacity.